KARAKTERISTIK ARANG KAYU KARET (HEVEA BRASILIENSIS) YANG DIPRODUKSI MENGGUNAKAN DUA TIPE TUNGKU PIROLISIS - Siti Mutiara Ridjayanti; Rahmi Adi Bazenet; Irwan Sukri Banuwa; Melya Riniarti; Wahyu Hidayat (Jurnal Belantara, 2023)
As the largest natural rubber producing country after Thailand, Indonesia has an immense potential of rubberwood sources. Rubberwood waste is suitable for raw materials to produce charcoal through pyrolysis method, providing more value-added. Kilns used in the pyrolysis process are diverse. The different kiln used will affect the characteristics of the charcoal produced. This study aimed to determine the characteristics of rubberwood charcoal produced using box-type kiln and dome-type kiln. The characteristics analyzed were charcoal yield, moisture content, ash content, volatile matter, and fixed carbon. The results showed dome and box-type kilns produced charcoals with different characteristics. Char yield of charcoal produced using box and dome-type kilns was 15.82% and 14.21%. Charcoal produced using box-type kiln has a moisture content of 4.51%, ash content of 3.06%, volatile matter of 18.10%, and fixed carbon of 74.33%, while charcoal produced using dome-type kiln has a moisture content of 6.16%, ash content 2.52%, volatile matter of 6.26%, and fixed carbon of 85.06%. The charcoal characteristics met the SNI 01-1683-1989 standard, except for the moisture content of charcoal produced using dome-type kiln.